Identificação de polimorfismos no Flowering Locus T (FT) e sua expressão gênica em diferêntes espécies do gênero Coffea - Cardon, Carlos Henrique (2016)
Due to the great economic and social importance of coffee, mainly to Brazil, the largest producer and exporter in the world, a better understanding of management techniques is of great importance in order to improve product quality and reduce production costs. One of the biggest problems faced by coffee growers is the sequential and asynchronous flowering of coffee trees, which increases production costs for the production of a good quality product. A better knowledge of the genes involved in flowering can be the key to the understanding the feature of the sequential flowering found in coffee trees, which although several studies have been conducted to improve the knowhow on the phenomenon, little is known so far. about its main causes. The gene FLOWERING LOCUS T (FT) is one of the key genes during the induction of flowering in various species. Polymorphism in the promoter region of the genes may be decisive in changing the behavior of their expression, since on their promoter regions are located binding motifs sequences of transcription factors essential in the regulation of expression. In order to better understand the action of FT on coffee flowering, this study aimed to compare the putative polymorphisms of the FT promoter region, as well as its expression pattern, in four different coffee species, Coffea arabica, Coffea canephora, Coffea eugenioides and Coffea racemosa, with different flowering features. Some of the motifs found were from binding regions of cis-regulatory elements linked to flowering regulation, which may act on the control of FT expression in coffee trees. Although it was not found a relationship between the FT expression pattern and the flowering features of the genotypes analyzed in this study, the identification of transcription factor binding motifs controlled by stimuli related to coffee flowering induction, shows that coffee FT may play a fundamental role in understanding the asynchronous coffee flowering.